1991
DOI: 10.1021/bi00223a028
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in 5S DNA and 5S RNA have different effects on the binding of Xenopus transcription factor IIIA

Abstract: The effects on TFIIIA binding affinity of a series of substitution mutations in the Xenopus laevis oocyte 5S RNA gene were quantified. These data indicate that TFIIIA binds specifically to 5S DNA by forming sequence-specific contacts with three discrete sites located within the classical A and C boxes and the intermediate element of the internal control region. Substitution of the nucleotide sequence at any of the three sites significantly reduces TFIIIA binding affinity, with a 100-fold reduction observed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
40
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…2B) with 3Ј boundaries at approximately positions ϩ69, ϩ80, ϩ93, and ϩ130 with respect to the transcriptional start site. TFIIIA bound to an uncomplexed X. borealis somatic 5S rRNA gene has been shown to occupy nucleotides ϩ45 to ϩ97 (32), with residues ϩ81 to ϩ91 forming the minimal requirements for TFIIIA binding (48). Thus, presumably, the fraction of mono- nucleosomes reconstituted on Xlo(Ϫ833ϩ136) which binds TFIIIA would be that with the TFIIIA binding site partially exposed (nucleosomes with 3Ј boundaries at nucleotides ϩ69 and ϩ80).…”
Section: Resultsmentioning
confidence: 99%
“…2B) with 3Ј boundaries at approximately positions ϩ69, ϩ80, ϩ93, and ϩ130 with respect to the transcriptional start site. TFIIIA bound to an uncomplexed X. borealis somatic 5S rRNA gene has been shown to occupy nucleotides ϩ45 to ϩ97 (32), with residues ϩ81 to ϩ91 forming the minimal requirements for TFIIIA binding (48). Thus, presumably, the fraction of mono- nucleosomes reconstituted on Xlo(Ϫ833ϩ136) which binds TFIIIA would be that with the TFIIIA binding site partially exposed (nucleosomes with 3Ј boundaries at nucleotides ϩ69 and ϩ80).…”
Section: Resultsmentioning
confidence: 99%
“…The factor makes multiple contacts over much of the nucleic acid through the nine zinc finger domains of the protein (8,9). Recognition is mediated by the secondary structure of the RNA with the major determinants located in a central domain composed of helix II-loop A-helix V-loop E (10). The other protein involved in the storage of cytoplasmic 5 S rRNA, p43, also contains nine zinc finger domains; however, it shares only 33% amino acid identity with TFIIIA (11).…”
mentioning
confidence: 99%
“…This might be due to the effects of the IE and BoxA in the affinity to the Transcription Factor IIIA (TFIIIA) compared to the BoxC. 29,30,31 It has been shown that BoxC interacts with the first 3 amino-terminal fingers of the TFIIIA, and that these are required for affinity to the 5S rDNA. 32,33 This may be the reason why BoxC is highly conserved among individuals.…”
Section: Resultsmentioning
confidence: 99%